Quantifying the effect of microbial diversity and plant roots on soil structural development - Martin, Sarah L. (2010)
Soil is one of the most complex ecosystems in the environment and changes to microbial diversity are thought to affect the physical structure (and vice versa). A fundamental question addressed in this research, is how microbial communities influence the functioning of soil, particularly with respect to the development and maintenance of a soil’s physical structure. Using micro- and macrocosms of sieved (and therefore structureless) soil, the effects of time, soil texture, manipulated background microbial diversity, and Plantago lanceolata (± mycorrhizal fungi) on the development of soil structure were determined. Background microbial diversity was manipulated using the dilution technique to give a low (101) dilution or a high (106) dilution of the original soil. This resulted in greater bacterial diversity in the lower (101) dilution than in the higher (106) dilution when in the presence of mycorrhizal plants. However, background diversity was the same irrespective of dilution in soils with non-mycorrhizal plants (and reversed within the bare soil). Micro- and macrocosms were continually assessed during controlled incubation periods ranging from 7 weeks to 15 months. Of the soil textures analysed (clay loam, loamy sand and sandy loam), loamy sand displayed the highest overall porosity as well as a noteworthy development in porosity throughout the incubation period. Mycorrhizal and nonmycorrhizal plants increased the speed of soil structural development by 5 months relative to unplanted soils. Although mycorrhizal fungi stunted root growth initially, aggregates within mycorrhizal planted treatments were smaller but nonetheless more stable than those in bare soil. Increasing mycorrhizal fungal species richness enhanced root and shoot biomass and reduced aggregate size and total porosity. There was a positive relationship between total porosity and numbers of culturable bacteria and fungi. In soils containing a lower microbial diversity, an increase in porosity, mean pore size, aggregate size and pore perimeter was observed. Results obtained were dependent on incubation conditions, planting regime and mycorrhizal status. Therefore, the effects of reducing microbial species diversity on soil structure parameters are idiosyncratic, with the presence of plant roots acting as a key factor.